One-step waferscale synthesis of 3-D ZnO nanosuperstructures by designed catalysts for substantial improvement of solar water oxidation efficiency - Liu, Chao; Xu, Xiaobin; Rettie, Alexander J. E.; Mullins, C. Buddie; Fan, D. L. (Journal of materials chemistry. A, Materials for energy and sustainability, 2013)
We investigated a rational mechanism for one-step waferscale synthesis of ZnO three dimensional (3-D) nanosuperstructures using designed catalysts viachemical vapor deposition. By precisely engineering the morphology and chemistry of the catalysts, we obtained 3-D nanosuperstructures from one dimensional (1-D) nanowire and two-dimensional (2-D) network catalysts (porous gold) in one-step. Tuning the material chemistry along the lengths of the nanowire catalysts yielded 3-D ZnO nanosuperstructures with distinct morphology on each segment. The growth mechanism and roles of chemistry of catalysts in growth of ZnO nanosuperstructures were studied. Compared with nanowire arrays synthesized from commonly used zero-dimensional (0-D) dot catalysts, 3-D nanosuperstructures significantly enhanced water oxidation efficiency by 150%. This work may inspire a new general paradigm for synthesis of 3-D semiconductor nanostructures as electrode materials for various energy related applications.